John Carvel Arnold papers - Arnold, John Carvel, 1833-1865.
Principally correspondence of Arnold with his wife, Mary Ann, while he served in the 49th Regiment of Pennsylvania Infantry and Mrs. Arnold's correspondence with their children, concerning his views on the military situation in Virginia and Maryland (1864-1865), the Copperheads, the rebels, army rations and pay, family finances, and her problems of maintaining a home and educating the children.
Typewritten transcripts of forty letters are available.
Laborer and Union soldier.
Collection material in English.
Keywords: Copperhead movement; Arnold, Mary Ann, -- active 1861-1895.; United States. -- Army. -- Pennsylvania Infantry Regiment, 49th (1861-1865); Maryland -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Women; Virginia -- History -- Civil War, 1861-1865.; Laborers; Soldiers